2014
DOI: 10.12944/cwe.9.2.40
|View full text |Cite
|
Sign up to set email alerts
|

The potential use of arbuscular mycorrhiza in the cultivation of medicinal plants in Barak Valley, Assam: A Review

Abstract: AM fungi are widespread and are found from arctic to tropics in most agricultural and natural ecosystems. They play an important role in plant growth, health and productivity. They increase seedling tolerance to drought, high temperatures, toxic heavy metals, high or low pH and even extreme soil acidity. The cultivation of medicinal and herbal plants has assumed greater importance in recent years due to their tremendous potential in modern and traditional medicine. They are also used as raw materials for pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Arbuscular mycorrhizal fungi play an important role in plant growth, health and productivity. AMF fungi help plants to absorb nutrients, especially the less available mineral nutrients such as copper, molybdenum, phosphorus and zinc (Chanda et al, 2014) AMF fungi have been shown to have benefits to host plants by increasing herbivore tolerance, pollination, soil stability, and heavy metal tolerance (Hart and Trevors 2005). Arbuscular mycorrhizal fungi help plant species to uptake water and nutrients and make physiological changes to increase growth and productivity of host plants, AMF fungi play a key role in soil fertility and plant nutrition, enhancing the uptake and translocation of mineral nutrients (P, N, S, K, Ca, Fe, Cu and Zn) from soil to host plants, by means of an extensive below ground hyphal network, which spreads from colonized roots into the soil environment (Smith and Read 2008 and Raei and Weisany 2013)…”
Section: 3 Oil Percentage Oil Yield / Plant and Oil Yield Feddan -1mentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi play an important role in plant growth, health and productivity. AMF fungi help plants to absorb nutrients, especially the less available mineral nutrients such as copper, molybdenum, phosphorus and zinc (Chanda et al, 2014) AMF fungi have been shown to have benefits to host plants by increasing herbivore tolerance, pollination, soil stability, and heavy metal tolerance (Hart and Trevors 2005). Arbuscular mycorrhizal fungi help plant species to uptake water and nutrients and make physiological changes to increase growth and productivity of host plants, AMF fungi play a key role in soil fertility and plant nutrition, enhancing the uptake and translocation of mineral nutrients (P, N, S, K, Ca, Fe, Cu and Zn) from soil to host plants, by means of an extensive below ground hyphal network, which spreads from colonized roots into the soil environment (Smith and Read 2008 and Raei and Weisany 2013)…”
Section: 3 Oil Percentage Oil Yield / Plant and Oil Yield Feddan -1mentioning
confidence: 99%
“…This result was supported by Maffia et al (1993) that Glomus, Acaulospora, and Gigaspora were observed in the Piperaceae rhizosphere, the genus Scutellospora cannot be found in this study. AMF can be utilized in increasing plant growth, including medicinal plants (Thapa et al, 2015;Chandra et al, 2014). According to Gogoi & Sigh (2011), AMF has an effect on the growth of Piper longum (Gogoi & Sigh, 2011;Seema & Garampalli, 2015) and P. nigrum (da Luz et al, 2015).…”
Section: Diversity Of Amfmentioning
confidence: 99%
“…Previously, there was not research, which has been done on AMF in rhizosphere of wati plant (P. methysticum) and in lowland area of Merauke, which having low pH. The plant species of P. methysticum are known to contain a fairly high metabolite (Tanjung et al, 2014), but AMF can be well-associated (Chandra et al, 2014). In fact, besides AMF, various plant species are also able to associate with endophytes (Cape et al, 2014;Hasanah et al, 2017).…”
Section: Diversity Of Amfmentioning
confidence: 99%
See 1 more Smart Citation
“…They can make the event possible through enhancing the uptake and translocation of mineral nutrients like phosphorous, nitrogen, sulphur, potassium, calcium, iron, copper and zinc from soil to the host plants. AM fungi associated with the medicinal plants are also known to enhance the plant growth and improve the active metabolites (Chanda et. al, 2014).…”
Section: Introductionmentioning
confidence: 99%